A multi-omics investigation into the mechanisms of hyper-virulence in Mycobacterium tuberculosis. Issue 1 (31st December 2022) - Rajwani, Rahim; Galata, Chala; Lee, Annie Wing Tung; So, Pui-Kin; Leung, Kenneth Siu Sing; Tam, Kingsley King Gee; Shehzad, Sheeba; Ng, Timothy Ting Leung; Zhu, Li; Lao, Hiu Yin; Chan, Chloe Toi-Mei; Leung, Jake Siu-Lun; et al.
ABSTRACT: Clinical manifestations of tuberculosis range from asymptomatic infection to a life-threatening disease such as tuberculous meningitis (TBM). Recent studies showed that the spectrum of disease severity could be related to genetic diversity among clinical strains of Mycobacterium tuberculosis (Mtb). Certain strains are reported to preferentially invade the central nervous system, thus earning the label "hypervirulent strains".However, specific genetic mutations that accounted for enhanced mycobacterial virulence are still unknown. We previously identified a set of 17 mutations in a hypervirulent Mtb strain that was from TBM patient and exhibited significantly better intracellular survivability. These mutations were also commonly shared by a cluster of globally circulating hyper-virulent strains. Here, we aimed to validate the impact of these hypervirulent-specific mutations on the dysregulation of gene networks associated with virulence in Mtb via multi-omic analysis. We surveyed transcriptomic and proteomic differences between the hyper-virulent and low-virulent strains using RNA-sequencing and label-free quantitative LC-MS/MS approach, respectively. We identified 25 genes consistently differentially expressed between the strains at both transcript and protein level, regardless the strains were growing in a nutrient-rich or a physiologically relevant multi-stress condition (acidic pH, limited nutrients, nitrosative stress, and hypoxia). Based on integrated genomic-transcriptomic and proteomic comparisons, the hypervirulent-specific mutations in FadE5 (g. 295, 746 C >T), Rv0178 (p. asp150glu), higB (p. asp30glu), and pip (IS 6110 -insertion) were linked to deregulated expression of the respective genes and their functionally downstream regulons. The result validated the connections between mutations, gene expression, and mycobacterial pathogenicity, and identified new possible virulence-associated pathways in Mtb .